DAMPAK PEMBERIAN KREDIT OLEH KOPERASI PENGEMBANGAN EKONOMI MASYARAKAT PESISIR (KOPPEMP) TERHADAP PENDAPATAN NELAYAN TANGKAP KECAMATAN TANJUNG MUTIARA KABUPATEN AGAM PROVINSI SUMATERA BARAT - Eni Yulinda; Zulkarnaini '; Nofri Antoni (Fakultas Perikanan dan Kelautan, Universitas Riau, 2011)
These research was conducted from May 12nd to June 12nd 2008 inTanjung Mutiara district, Agam sub province, west sumatera province. Thepurpose of this research was to understand the process of implementation of creditby KOPPEMP to fishermen and to know its impact toward their incomes. Thisresearch used survey Method. From the research result known that: Their averagefisherman net income before receiving credit was Rp. 17.407.416,67/year, whileafter receiving credit was Rp. 19.995.229,17/year,increase 14.87%. The incomeof fishermen before receiving credit from different KOPPEMP with real incomeafter receiving KOPPEMP of credit.